Malignant transformation of desmoplastic infantile tumors in a non-infant: a case report - Yang, Yan; Tian, Bin; Chen, Xuzhu; Liu, Xin; Li, Shiguang (Frontiers in Oncology, 2023)
Desmoplastic infantile tumors (DITs) are rare benign intracranial tumors in infants with benign biological behavior and rare malignant transformation characteristics. We present a DIT case that underwent malignant transformation and metastasis. A 6-year-old girl presented with DITs and underwent surgical resection. 12 years later, the tumor recurred and underwent surgical resection again. The pathology report confirmed the lesion to be a glioblastoma multiforme. She received adjuvant treatment. A year after the surgical operation of the lesions, she had intraspinal metastasis and underwent surgical resection again. Multiple spinal cord metastases were subsequently identified in the patient. The patient’s condition exhibited severe deterioration during the follow-up period. This case report focuses on the occurrence of DITs and their potential malignant transformation, as assessed through computed tomography and magnetic resonance imaging.